2019
DOI: 10.1016/j.celrep.2018.12.071
|View full text |Cite
|
Sign up to set email alerts
|

p53 Loss in Breast Cancer Leads to Myc Activation, Increased Cell Plasticity, and Expression of a Mitotic Signature with Prognostic Value

Abstract: SummaryLoss of p53 function is invariably associated with cancer. Its role in tumor growth was recently linked to its effects on cancer stem cells (CSCs), although the underlying molecular mechanisms remain unknown. Here, we show that c-myc is a transcriptional target of p53 in mammary stem cells (MaSCs) and is activated in breast tumors as a consequence of p53 loss. Constitutive Myc expression in normal mammary cells leads to increased frequency of MaSC symmetric divisions, extended MaSC replicative-potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 86 publications
3
58
0
Order By: Relevance
“…Chemotherapy is the most common type of treatment, where chemicals or drugs to destroy cancer cells and cancer microenvironments are applied. Genomic studies such as those on TP53, BCL2, and c-MYC have accelerated the effective application of chemotherapy for developing anticancer drugs and reagents in cancer treatment [48][49][50]. Anticancer drugs, according to their mechanisms of action, are generally classified as either alkylating agents for damaging cancer cell DNA, antimetabolites for replacing the normal building blocks of RNA and DNA, or antibiotics for interfering with the enzymes involved in DNA replication [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…Chemotherapy is the most common type of treatment, where chemicals or drugs to destroy cancer cells and cancer microenvironments are applied. Genomic studies such as those on TP53, BCL2, and c-MYC have accelerated the effective application of chemotherapy for developing anticancer drugs and reagents in cancer treatment [48][49][50]. Anticancer drugs, according to their mechanisms of action, are generally classified as either alkylating agents for damaging cancer cell DNA, antimetabolites for replacing the normal building blocks of RNA and DNA, or antibiotics for interfering with the enzymes involved in DNA replication [51][52][53].…”
Section: Discussionmentioning
confidence: 99%
“…c‐Myc is an important cancer‐associated TF and promotes tumor cell growth and proliferation by regulating numerous target genes such as Cdc25A , hTERT , and glutamine synthetase 15‐17 . Santoro et al 18 reported that p53 loss induces c‐Myc activation in breast tumors. Although c‐Myc is important for symmetric cell division of mammary stem cells and induces reprogramming of progenitor cells to stem cells in a mouse model, concomitant p53 loss and c‐Myc activation upregulates expression of 189 mitosis‐associated genes, resulting in the expansion of cancer stem cells in human breast cancer cells.…”
Section: Cancer‐associated Tfs Are a Promising Target For Cancer Therapymentioning
confidence: 99%
“…The risk curve can clearly show the relationship between survival status, survival time and expression of CSCs and risk score (Fig. 1F) [17]. The univariate Cox regression showed factors related to prognosis like a stage, T, M, N and risk score (P < 0.05), while multivariate Cox regression showed that only stage and risk score were signi cant independent risk factor of LUAD.…”
Section: Construction Of Signaturementioning
confidence: 91%